PELATIHAN BANK REKONSILIASI PERUSAHAAN JASA BAGI SISWA/I SMA KRISTEN YUSUF - Elsa Imelda; Alyssa Christina; Jolin Jolin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
This activity has the aim of providing training and understanding to Yusuf Christian High School students about bank reconciliation. Students are expected to be able to produce bank reconciliation reports for service companies. At the last stage, a quiz was given to the trainees to determine their level of understanding of the material previously described. The results of the assessment showed that the participants had understood the material well. The results of the questionnaire also showed that the material provided was useful for them.